2014
DOI: 10.1007/s40506-014-0025-1
|View full text |Cite
|
Sign up to set email alerts
|

Dengue: Moving from Current Standard of Care to State-of-the-Art Treatment

Abstract: Opinion statementTreatment of dengue remains supportive in the absence of targeted antiviral therapy or approved vaccines. Responsive fluid management is key to preventing progression to shock or other severe manifestations. The dynamic natural history of dengue infection and its influence on hemodynamic homeostasis needs to be carefully considered in the planning of individualized therapy. Though largely self-limiting, the sheer burden of dengue disease on the global population will result in atypical manifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 133 publications
(119 reference statements)
0
18
0
1
Order By: Relevance
“…Hypoalbuminemia, one parameter of the Dengue Score, has been reported to be a cause of fluid accumulation, and this condition could be used as a surrogate marker for severe plasma leakage [ 22 , 23 ]. Thein et al [ 24 ] reported that a combination of three variables, i.e., hemoconcentration, rapid decrease in platelet count, and fluid accumulation, had high specificity for predicting severe dengue.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoalbuminemia, one parameter of the Dengue Score, has been reported to be a cause of fluid accumulation, and this condition could be used as a surrogate marker for severe plasma leakage [ 22 , 23 ]. Thein et al [ 24 ] reported that a combination of three variables, i.e., hemoconcentration, rapid decrease in platelet count, and fluid accumulation, had high specificity for predicting severe dengue.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these signs and symptoms, health providers need to correctly assess, diagnose, and treat dengue to decrease the length of stay and complications [16] because the death rate of dengue patients is 30% [14]. A study showed the necessity of appropriate health provider treatment and/or evidence-based management guidelines [19]. Then, the area needs to develop the appropriate DCPG.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no effective treatment for DENV infections. The first DENV vaccine was recently licensed for use after several decades of efforts, unfortunately, it confers only partial protection to all DENV serotypes (Gan, 2014 ; Thisyakorn and Thisyakorn, 2014 ).…”
Section: Introductionmentioning
confidence: 99%